A randomized controlled clinical trial evaluating the effect of Trigonella foenum-graecum (fenugreek) versus glibenclamide in patients with diabetes - Najdi, Rania A; Hagras, Magda M; Kamel, Fatemah O; Magadm, Rania M (African health sciences, 2019)
Background: Herbal medicines long have been used in the management of diabetes mellitus (DM). Objective: This study was conducted to ascertain if fenugreek compared with glibenclamide had any impacts on controlling blood glucose in patients with uncontrolled type II DM on conventional therapy. Methods: A total of 12 patients with uncontrolled DM and on metformin were recruited and divided into two groups. Patients in group 1 received 2 g fenugreek per day, whereas those in group 2 received glibenclamide 5 mg once daily. The impacts of fenugreek on the glycemic control and lipid profile were measured before initiation of the regimen and then after 12 weeks. Results: Only 9 of the 12 study participants completed the study. Fenugreek at 2 g/day caused an insignificant drop in fasting blood glucose (P = 0.63), but the fasting insulin level increased significantly (P = 0.04). The ratio of high- to low-density lipoprotein was significantly decreased from before to after treatment (P = 0.006). Fenugreek did not cause any notable adverse impacts on hepatic and renal functions throughout the study. Conclusion: Fenugreek could be used as adjuvant therapy to anti-diabetic drugs to control blood glucose, and further studies are needed. DOI: https://dx.doi.org/10.4314/ahs.v19i1.34 Cite as: Najdi RA, Hagras MM, Kamel FO, RM M. A randomized controlled clinical trial evaluating the effect of Trigonella foenum-graecum (fenugreek) versus glibenclamide in patients with diabetes. Afri Health Sci. 2019;19(1). 1594-1601. https://dx.doi.org/10.4314/ahs.v19i1.34